Perceived product reputation, brand commitment, and corporate social responsibility as predictors of customer satisfaction - Famakinde, Oluwafemi P.; Omolaja, Lukman O. T.; Uye, Emmanuel E. (Universitas Airlangga, 2024)
Customers are the end goal for every business as they create demand and revenue for the business organization. In order to retain customers, businesses need to identify what customers expect from them. One of the least studied businesses is the paint industry. The study filled this gap in knowledge by investigating perceived product reputation, brand commitment and corporate social responsibility as predictors of customer satisfaction among paint buyers in Lagos, Nigeria. A cross-sectional survey research design was used, while a purposive sampling technique was utilized to select two local government areas in Lagos State. Data were collected from 274 paint buyers using validated scales and analyzed with a t-test of independent samples and multiple regression analysis. The result indicates that perceived product reputation, brand commitment and corporate social responsibility jointly predicted customer satisfaction among paint buyers. Furthermore, perceived product reputation, brand commitment and corporate social responsibility independently predicted customer satisfaction. The conclusion is that perceived product reputation, brand commitment, and corporate social responsibility are robust predictors of customer satisfaction among study participants. The study recommends that paint companies continue to improve their branding policy and corporate social responsibility to retain and capture potential consumers in the paint industry.